RATING SYSTEMS FOR SCIENTOMETRIC INDICES OF UNIVERSITIES: KEY ASPECTS, DEVELOPMENT, IMPLEMENTATION - Spivakovsky, O.; Vinnyk, M.; Poltoratskiy, M.; Tarasich, Y.; Bystriantseva, A.; Panova, K.; Spivakovska, Y. (Journal of Information Technologies in Education (ITE), 2018)
Our time is characterized by the phenomenal acceleration of knowledge accumulation and the complication of its structure. Today information technologies are one of main ways to arrange and create effective tools for organizing the interaction and processing large amount of information. Nowadays academic institutions need to rely on special research, analysis of accumulated achievements and, on this basis, to develop forecasts, identify trends and prospects for the development of a scientific or other industry, and evaluate its potential. Today many information systems attempt to create methods and technologies of processing and saving information on the activities of scientists. The article provides a brief overview of rating systems for scientometric indices of universities. In our opinion, information of university’s scientific activity should be presented in the rating form, which gives an opportunity to analyze development in different directions and changes. The key idea of the article is presenting of our experience in developing system of automatic construction of ratings of scientific organizations based on their scientometric indicators in Scopus, Google Scholar and Web of Science. The main task of the system is automatic construction of consolidated rating of scientists, research groups, and organizations according to indicators of processed scientometric systems (Scopus, Google Scholar and Web of Science). These indicators are h-index, citations (numbers of total citations of documents that are indexed by the system), total number of scientist’s publications. The philosophy of the system is providing open data of different scientometric systems, and possibility to deploy our system in other organizations and customize it for individual goals and tasks.